Patient advocates' views of patient roles in interprofessional collaborative practice in primary care: A constructivist grounded theory study. (22nd September 2022) - Davidson, Alexandra R.; Morgan, Mark; Ball, Lauren; Reidlinger, Dianne P.
Abstract: Interprofessional collaborative practice has been shown to be an appropriate model of care for chronic disease management in primary care. However, how patients play a role in this model is relatively unknown. The aim of this constructivist grounded theory focus group study was to explore the perceptions of patient advocates regarding the role of patients in interprofessional collaborative practice for chronic conditions in primary care. Primary data were collected from patient advocates, from public and private Australian organisations and who represent patients with chronic disease in primary care, through focus groups in July–August 2020. Videoconference focus groups were recorded, transcribed verbatim and inductively, thematically analysed using the five‐step approach by Charmaz: (1) initial line‐by‐line coding, (2) focused coding, (3) memo writing, (4) categorisation and (5) theme and sub‐theme development. Three focus groups comprising 17 patient advocates with diverse cultural and professional backgrounds participated. Two themes and five sub‐themes relating to interprofessional collaborative practice teams were constructed from the data. In theme 1, patients 'shifted across the spectrum of roles' from 'relinquishing control to the team', 'joining the team' to 'disengaging from the team'. The second theme was the need for 'juggling roles' by 'integrating patient role with life roles', and 'learning about the patient role'. The diversity and variability of patient roles as described by patient advocates highlight the challenges of working with people with chronic conditions. The diverse patient roles described by advocates are an important finding that may better inform communication between patients and health professionals when managing chronic conditions. From the health professional perspective, identification of the role of a patient may be challenging. Therefore, future research should explore the development of a tool to assist both patients and health professionals to identify patient roles as they move across the spectrum, with the support of policy makers. This tool should aim to identify and promote patient engagement in interprofessional collaborative practice in primary care settings.